Treatments to post-stroke depression, which is more effective to HAMD improvement? A network meta-analysis - Zhang, Jie; Song, Zhaoming; Gui, Chen; Jiang, Guannan; Cheng, Wei; You, Wanchun; Wang, Zhong; Chen, Gang (Frontiers in Pharmacology, 2022)
Background: Post-stroke depression (PSD) is a common mental health problem after cerebrovascular accidents. There are several treatments that have been shown to be effective in treating post-stroke depression. However, it is not clear which treatment is more effective. Methods: In this meta-analysis, an appropriate search strategy was used to search eligible randomized controlled trials (RCTs) on different treatments to treat patients with PSD published up to December 2021 from the CNKI, PubMed, and Cochrane Library. We assessed the mean difference or odds ratio between each treatment and placebo and summarized them as the average and 95% confidence interval (CI) by conducting Bayesian network meta-analyses. Results By constructing a Bayesian network meta-analysis, we found that acupuncture combined with fluoxetine (vs. placebo MD, -8.9; 95% CI, [-15, -2.9]) or paroxetine (vs. placebo MD, - 8.5; 95% CI, [-15, -2.5]) was the most effective for change in Hamilton depression scale (HAMD) at the end of the 4th week. For change in HAMD at the end of the 8th week, rTMS combined with paroxetine (vs. placebo MD, -13; 95% CI, [-17, -7.9]) had the greatest amount of change. The efficacy of medication combined with adjuvant therapy was also superior for the percentage of patients with HAMD change over 50%. Conclusion The combination of antidepressants with adjuvant therapy may enhance the efficacy of antidepressants and achieve better results than antidepressant monotherapy in both HAMD changes at the end of week 4 or 8 and 50% HAMD improvement rate. Acupuncture combined with fluoxetine treatment was more effective in the treatment of post-stroke depression at week 4, while rTMS combined with paroxetine was more effective at week 8. Further research is needed to determine whether acupuncture combined with fluoxetine is better than rTMS combined with paroxetine for post-stroke depression at week 8.